Lonely heroes - García Lozano, Francisco José (Razón y fe, 2018)
The disappearance of great stories and great political,  social and religious projects, as outlining signs of modernity, does not suppose, on the contrary, an exhaustion, cloisture or closure of its most stimulating projections. The images that these cultural conglomerates created have not disappeared, and no matter how hard they try to silence them, mythologies always return, summoned by recurring crises and by the extreme situations that men face. A logos that does not finish crystallizing and myths that do not stop emerging, with new images that are a better reflection of current times. The classic romantic hero of the Byronian style, filled with a tragic nature, has been replaced by the modern "outsider", less tormented but equally marked by loneliness, isolation and difference, condemned by his destiny. Drive, by Nicolas Winding Refn, and The Mole, by Tomas Alfredson, are two good examples of these hypnotic characters marked by doom, under whose sign they drift.